THE DEVELOPING SPEAKING COMPETENCES IN SIMULTANEOUS INTERPRETATION - Kodirova, Shokhsanam Alisher kizi (Educational Research in Universal Sciences, 2023)
This article observes main approaches to developing speaking competences in simultaneous interpretation. Development of speaking competences in the field of interpretation differs from developing the same skills in foreign language acquisition. Moreover, interpretation classes should be dedicated to teaching basic interpretational techniques.